The advanced lung cancer inflammation index predicts long-term outcomes in patients with hypertension: National health and nutrition examination study, 1999–2014 - Zhang, Yanbin; Pan, Yuxiong; Tu, Jiabin; Liao, Lihua; Lin, Shuqiong; Chen, Kaihong; Ding, Shan; Xiao, Guitao (Frontiers in Nutrition, 2022)
Background: Malnutrition and systemic inflammation are associated with poor outcomes in patients with hypertension, and the two often coexist. However, few studies have combined nutritional and inflammatory status to assess the prognosis of patients with hypertension. The present study aimed to investigate the association between advanced lung cancer inflammation index (ALI), as a factor assessment the nutritional and inflammatory status, and long-term all-cause mortality of patients with hypertension. Method: Data from the National Health and Nutrition Examination Survey (NHANES) 1999–2014 with mortality follow-up through December 31, 2015, were analyzed. A total of 15,681 participants were evaluated. The patients were grouped based on the ALI tertiles as follows: T1 (ALI≤49.41, n = 5,222), T2 (ALI>49.41 and ≤76.29, n = 5,221), and T3 (ALI>76.29, n = 5,237) groups. Survival curves and Cox regression analysis based on the NHANES recommended weights were used to assess the relationship between nutritional and inflammatory status and long-term all-cause mortality. Results: ALI was significantly associated with long-term all-cause mortality in patients with hypertension. After adjustment for related factors, the T2 [hazard ratio (HR): 0.69, 95% confidence interval (CI): 0.58−0.83; P < 0.001) and T3 (HR: 0.59, 95% CI: 0.47−0.74; P < 0.001) groups were significantly associated with a decreased risk of all-cause mortality compared to the lower ALI level group (T1). Conclusions: ALI was a comprehensive index of nutrition and inflammation and an independent significant prognostic factor in hypertension patients in the American community. Systemic inflammatory and nutritional status assessment and monitoring are essential for the health of hypertensive patients.